2009
DOI: 10.1117/1.3147407
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled carbon nanotubes as a multimodal-thermoacoustic and photoacoustic-contrast agent

Abstract: Abstract. We have developed a novel carbon nanotube-based contrast agent for both thermoacoustic and photoacoustic tomography. In comparison to deionized water, single-walled carbon nanotubes exhibited more than twofold signal enhancement for thermoacoustic tomography at 3 GHz. In comparison to blood, they exhibited more than sixfold signal enhancement for photoacoustic tomography at 1064 nm wavelength. The large contrast enhancement of singlewalled carbon nanotubes was further corroborated by tissue phantom i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
134
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 42 publications
(50 reference statements)
0
134
1
1
Order By: Relevance
“…[8][9][10][11][12][13] Recently, investigations have sought to improve PAT/TAT performance. [14][15][16][17] The results showed that PAT/TAT was capable of high-resolution structural, functional, and molecular imaging that was free of speckle artifacts. Combinations of PAT/TAT or PAT/US were investigated for breast cancer and sentinel lymph node imaging.…”
Section: Introductionmentioning
confidence: 86%
“…[8][9][10][11][12][13] Recently, investigations have sought to improve PAT/TAT performance. [14][15][16][17] The results showed that PAT/TAT was capable of high-resolution structural, functional, and molecular imaging that was free of speckle artifacts. Combinations of PAT/TAT or PAT/US were investigated for breast cancer and sentinel lymph node imaging.…”
Section: Introductionmentioning
confidence: 86%
“…SWNTs can offer more than twofold signal amplification in thermoacoustic tomography (TAT) and more than sixfold signal enlargement in photoacoustic tomography (PAT) compared with control. Due to SWNTs being able to give maximum signal compared with other carbon materials, fullerenes, and graphitic microparticles, this characteristic makes them applicable in the PAI as ideal contrast-mediums [78].…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…Carbon nanomaterials have been considered as potential biomedical materialsfor pharmaceutical, biomedical, [357,358] and bio-imaging applications, [359][360][361][362] including PAI [363][364][365][366][367][368][369][370][371][372] and thermo-acoustic imaging [373]. The characteristic optical properties of SWNTs, particularly those with optical properties in the NIR region, [374] play an important role in photoacoustic imaging [375].…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%